Endovascular skills : guidewire and catheter skills for endovascular surgery - Schneider, Peter A. (Boca Raton : CRC Press, 2019)
Since the first edition of this text was published, endovascular technique has become a mainstay of vascular care, treating disease that would have previously required open surgery. This book provides a step-by-step approach to endovascular intervention and aims to assist clinicians in the development and refinement of skills that are now essential
OCLC-licensed vendor bibliographic record.
Keywords: Blood-vessels -- Endoscopic surgery; Blood-vessels -- Interventional radiology; Peripheral vascular diseases -- Endoscopic surgery; Peripheral vascular diseases -- Interventional radiology; MEDICAL / General; MEDICAL / Cardiology; MEDICAL / Surgery / Thoracic